PERBEDAAN HASIL BELAJAR APRESIASI SENI RUPA ANTARA METODE ARTIKULASI DENGAN METODE KONVENSIONAL - Surya Afriza; Eswendi .; Efrizal . (Universitas Negeri Padang, 2012)
Abstract The purposes of this were to test different of the students’ result of study of visual art appreciation between articulation method with convensional method in SMP Negeriy 2 Sintuk Toboh Gadang, Pariaman. This research is experiment quacy through Design One Group Pretest - Postest. The Population is all of the student of 7 th of SMP Negeri 2 Sintuk Toboh Gadang, Pariaman. The technique of sampling was Purposive Sampling. Experimenth class was VII.4 and control class was VII.3. The result of study can be seen trought the result of study of visual art appreciation. The mean of students’ result of study the experiment class taller than the mean of result of study control class. After T-tes done, the researcher got count- T 2.520 and table – T 1.669 (count – T > table- T) Katakunci: Apresiasi, Artikulasi, Konvensional, Eksperimen, Kontrol.